Teacher’s time organization and its relationship to job satisfaction: Chilean case evidence - Cabezas, Veronica; Medeiros, María Paz; Inostroza, David; Gómez, Constanza; Loyola, Vicente (Education Policy Analysis Archives, 2017)
The literature indicates that teachers lack of time to adequately prepare and fulfill their responsibilities, is one of the key factors that negatively influence levels of teacher job satisfaction. Considering a representative sample of teachers in Santiago of Chile (N=950) and using conditional models, this study explores the relationship between teacher job satisfaction that work in subsidized schools, and the time available to these teachers for realizing activities over and above actual teaching hours: contracted non-teaching hours and additional overtime. This study uses a questionnaire that incorporates, in addition to the overtime, information about how teachers use their time, identifying the type of activities they are involved in, and if they are involved individually or as a group. The results indicate that there is a robust positive relationship between the number of contracted non-teaching hours and teacher job satisfaction, and a negative relationship with respect to overtime. Also identified the relevance of being adequately resourced with formal instances to engage in collaborative work for planning and prepare class materials, since it is linked to a positive effect on teacher job satisfaction.